Theoretical Model of Copyrighted Content Consumption - Bartkus, Algirdas (Ekonomika, 2025)
This paper deals with the price discrimination issue when a producer applies one price to a buyer in one selling location and another at another selling location for the same product. The specific case under consideration is the consumption of copyrighted products in television broadcasts and payment for them at home and in hotels. Unlike most articles where the analysis of price discrimination is based on the case of discounts to a specific group of consumers, this article deals with the opposite case, where a manufacturer of creative content raises the price for one group of customers compared to a standard group. The examination of the issue is based on a theoretical microeconomic model rather than on statistical data analysis because data on the amounts of copyright payments is unavailable. The main reason for the analysis, which is based on a theoretical model, is the lack of officially available data on payments to copyright agencies. Different agencies apply their own tariffs to all physical places where creative content can be consumed, and this data is not officially available. The lack of data is not a major obstacle because it would show how things are and not what choice would benefit society. The limitation of the data is that it does not show the motives of the choice but only states the choice itself. The advantage of theoretical modeling is that it allows one to analyze the outcomes with respect to the motives influencing the choice and action. The article attempts to answer the questions of whether the service provider’s decision to engage in pricing discrimination is a right choice for the provider and what the consequences of this action are for the consumers and society. Based on the analysis of choices, this article also aims to determine the conditions under which price discrimination can be considered a bad practice and when it should be tolerated. The first part of the paper presents a brief explanation of the problem, a literature survey that encloses the prevailing approaches and points of view on the issue of price discrimination. The second part contains a theoretical microeconomic model which allows for the evaluation of all the consequences that the producer and seller is facing when they pass different prices for different locations, and the consumer has a free choice to reject purchases if the price for them is not acceptable. The third part is devoted to the analysis of how different prices affect consumption, profits, and consumer utility. The final section is devoted to the conclusions that follow from this analysis. The microeconomic model is based on the unrestricted choice of the buyer when buyers themselves freely decide what amount of copyrighted content to buy at any of the selling places and on the unrestricted choice of the seller to set up the price that the seller deems appropriate. In the model, neither party of the transaction dominates nor can decide for the other party, but the choice of one party influences the decisions of the other party. The implications of the model, which is based on the rational choice of economic agents and not on current administrative practice, can be used for policy and legislative purposes.